A Closer Look at the Role of Nanometer Scale Solute-Rich Stacking Faults in the Localized Corrosion of a Magnesium Alloy GZ31K. Issue 7 (27th April 2018) - Zhang, X.; Kairy, S. K.; Dai, J.; Birbilis, N.
Abstract : The localized corrosion of as-cast Mg-3Gd-1Zn-0.4Zr (GZ31K) was investigated herein. Assessment of this alloy was carefully selected owing to the presence of chemically distinct stacking faults (SFs) in the α-Mg matrix. The role of a nanometer scale solute-rich SFs on localized corrosion was realized by quasi in-situ scanning transmission electron microscopy (STEM), supplemented by scanning electron microscopy (SEM) and electrochemical methods. It was determined that chemically distinct SFs were highly enriched in Gd and Zn. When the Mg-3Gd-1Zn-0.4Zr alloy was exposed to quiescent 0.1M NaCl, the α-Mg matrix at the periphery of solute-rich SFs was preferentially dissolved. In addition, re-deposition of Zn and Gd was observed upon the α-Mg matrix, accompanying matrix dissolution. Such findings elucidate the relative inertness of solute-rich SFs at this near atomic length scale for the first time, revealing both the nanoscale localized corrosion morphology and unambiguously revealing re-deposition of alloying elements at this scale. Distortion and disintegration of solute-rich SFs at corrosion sites indicate an evolution of stress during the α-Mg matrix dissolution and Mg oxide/hydroxide formation. Localized corrosion morphology on the micrometer scale revealed that the α-Mg matrix surrounding coarser eutectic phase particles was protected as a result of localized alkalinity by the eutectic phase.